Proyecto profesional fotográfico: fotolibro “lo que nos une”. Una perspectiva hacia la violencia de género desde una experiencia personal - Alania Torres, Jeny Dileta (2020)
The present work of professional sufficiency is the result of a research process on issues of violence and gender based on a personal event. The project describes the process of conceptualization and realization of the photobook “What unites us”. In the middle of last year my mother revealed her secret to me, one in which she was sexually and psychologically abused in her first engagement. It is from this event that my search for my mother's feelings begins; what she lived, her empowerment, her strength and her fears; in order to understand how I see myself reflected in all this. Likewise, understand that this situation goes beyond us and ends up being placed within a current problem in our country. Therefore, I believe that it still needs to be discussed and debated in public and private spaces.